Synthesis and electrochemical performance of aluminum antimonide alloy anode prepared by melt spinning - Kharistal, Daniel Julian (2014)
In this work we have successfully synthesized melt spun Al-Sb alloy and studied the electrochemical performance of these Al-Sb alloy as anodes for lithium ion batteries. The melt spun Al-Sb alloy has unique morphological structure compared to the conventional cast Al-Sb alloy. In high Al content the AlSb phase is surrounded by Al matrix while in high Sb content the AlSb acts as a matrix and surround the Sb phase. The size of the AlSb phase ranged from 0.1 to 1 μm, which is much smaller compared to the conventional cast Al-Sb alloy. Another advantage in using melt spinning process is that it can produce materials with high throughput and high purity metal alloy products with little to no impurities, which is beneficial to the battery performance. The melt spun Al-Sb alloy exhibited improved electrochemical performance with the first discharge capacity of 635 mAh/g, high Coulombic efficiency of 85%, and good cycling performance of 504 mAh/g after 80 cycles is exhibited by Al40Sb60 samples. A good electrochemical performance is also demonstrated by the Al50Sb50 samples with first discharge capacity of 600 mAh/g and after 80 cycles was able to maintain good capacity of around 470 mAh/g. We propose that the battery performance of the melt spun Al-Sb alloy is mainly influenced by the amount of AlSb phase in the structure and the ability of AlSb phase to reform itself after cycling. The ability of the AlSb phase to restructure and reform itself after reaction with lithium (dealloying) is crucial in order to maintain good battery performance and cycleability of the anodes. The Al60Sb40 and the Al50Sb50 demonstrated good battery performance due to the most of AlSb phase able to maintain structural integrity and not breakdown into individual Al and Sb phase upon cycling, as evidenced by the post mortem XRD characterization showing high amount of AlSb phase after lithiated for 100 cycles, while the Al80Sb20 and Al20Sb80 exhibited poor performance due to the large amount of inherent Al and Sb phase in the structure and the breakdown of some of the AlSb phase into individual Al and Sb particles. The breakdown of AlSb phase into individual Al and Sb particles has led to cracking and loss of electrode contact due to the large volume expansion created by Al and Sb phase reaction with lithium during cycling process. The discussed findings highlights the advantages of the melt spun Al-Sb alloys as anode and the possibilities for further development of this material as a potential candidate for the next generation of anode material for lithium ion batteries with superior electrochemical properties.